2019
DOI: 10.7759/cureus.3880
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Clinical Characteristics, and Management Status of Hepatitis B: A Cross-sectional Study in a Tertiary Care Hospital at Karachi, Pakistan

Abstract: BackgroundHepatitis B virus (HBV) infection is a serious health problem in Pakistan. In view of the serious socioeconomic consequences, identifying patient characteristics and the current treatment for the disease will enhance HBV regulation and its medical management.AimsTo describe the epidemiology, clinical characteristics, and current management status of patients infected by HBV.MethodsWe undertook an observational, cross-sectional, and epidemiological study at the Jinnah Postgraduate Medical Centre, Kara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…The phases are presented in Table 1. [13][14][15][16][17]. The aforementioned studies have all featured a male predominance among HBV-infected patients and the mean age was between 20-40 years, which is comparable to our cohort.…”
Section: Methodssupporting
confidence: 77%
“…The phases are presented in Table 1. [13][14][15][16][17]. The aforementioned studies have all featured a male predominance among HBV-infected patients and the mean age was between 20-40 years, which is comparable to our cohort.…”
Section: Methodssupporting
confidence: 77%
“…The HBV prevalence among the enrolled subjects was 5.24% (Table 1) and these infected subjects were having no knowledge of their HBV status. Similarly, a study conducted at a tertiary care hospital, Karachi reported that the subjects diagnosed with HBV were mainly students 11 . Another study conducted in Uganda, showed high prevalence of HBV among students 12 .…”
Section: Discussionmentioning
confidence: 91%
“…1455 were involved sharing personal items (comb, nail cutter, razors, towel, food pots and cosmetics). A study reported, roadside barbers as the major source of HBV spread after positive family history, followed by dental extraction, blood transfusion and Tattoos etc 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, almost all smokers were men, which reduced survival in men and, conversely, the absence of smokers among women improved survival rates. Men also have easier and greater access to healthcare facilities, which might have contributed to their predominant numbers [ 13 ]; however, despite previous reports, this remains an expert opinion at best.…”
Section: Discussionmentioning
confidence: 99%